2016
DOI: 10.1002/elps.201600016
|View full text |Cite
|
Sign up to set email alerts
|

Trace amounts of poly‐β‐cyclodextrin wrapped carbon nanotubes for the microextraction of flavonoids in honey samples by capillary electrophoresis with light‐emitting diode induced fluorescence detection

Abstract: A novel dispersive micro-SPE method with trace poly-β-CD wrapped multiwalled carbon nanotubes as sorbents was applied to extract flavonoids in honey samples. The analytes were then determined by CE with LED-induced fluorescence detection. The influencing parameters, such as the sorbent concentration, extraction time, and eluent type, were properly optimized. The established method had the advantages of simplicity, low consumption of sorbent amount (0.009 mg) and organic solvent (100 μL), and high sensitivity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…It was found that the PCD@CNTs exhibited some typical absorption features of the PCD, such as vibrations of glucose units at 1023 cm –1 (C–O stretching) and 1151 cm –1 (C–O–C stretching). A strong band was seen at 3417 cm –1 (O–H stretching), which confirmed the presence of hydroxyl groups in PCD@CNTs . These results demonstrated that all of the main functional groups in CNTs and PCD were presented in PCD@CNTs.…”
Section: Resultssupporting
confidence: 59%
“…It was found that the PCD@CNTs exhibited some typical absorption features of the PCD, such as vibrations of glucose units at 1023 cm –1 (C–O stretching) and 1151 cm –1 (C–O–C stretching). A strong band was seen at 3417 cm –1 (O–H stretching), which confirmed the presence of hydroxyl groups in PCD@CNTs . These results demonstrated that all of the main functional groups in CNTs and PCD were presented in PCD@CNTs.…”
Section: Resultssupporting
confidence: 59%
“…Another application of a sample pretreatment method followed by CE analysis was developed by Xu et al. , they used trace amounts of poly‐β‐cyclodextrin wrapped carbon nanotubes (poly‐β‐CD‐MWCNT) for the extraction of flavonoids in honey samples. After this extraction, the analytes were separated and determined by CE with light‐emitting diode induced fluorescence detection (LED‐IF).…”
Section: Phenols Polyphenols and Lipidsmentioning
confidence: 99%
“…Recently, DMSPE has been widely applied in the extraction and preconcentration of active compounds in natural products due to its unique advantages. Several selected applications involving the use of DMSPE in the analysis of TCMs are shown in Table 4 [93][94][95][96][97][98]. Among them, a schematic procedure for graphite oxide-assisted DMSPE is shown in Fig.…”
Section: Dmspementioning
confidence: 99%
“…Relatively low LODs ranged from 0.22 to 16.19 ng/mL, and satisfactory recovery in the range of 89-106% was obtained under the optimum conditions. Xu et al prepared poly-β-cyclodextrin-wrapped carbon nanotubes as an adsorbent in DMSPE for the extraction of flavonoids in honey samples[97]. The poly-β-cyclodextrin-wrapped carbon nanotubes improved the dispersibility of MWCNTs in aqueous solutions and provided high extraction efficiency of the target analytes with enrichment factors in the range of 78-166 due to the existence of van der Waals forces, π-π stacking, hydrophobic, and hydrogen bonding interactions between sorbent and target analytes.…”
mentioning
confidence: 99%